El pensamiento realista en la dependencia de Quito: Juan Martínez de Loayza - Paniagua Pérez, Jesús (Estudios humanísticos. Geografía, historia y arte, 1996)
In this article we present the shorter writings of Pedro Martínez de Loayza, a well-known churchmen, who defended the Royalist cause in the city of Cuenca (Ecuador) during the events which took place there in 1811. True to his ideas, he reflected in these writings the attitude which caused him to become one of the leading lights in the opposition to the threats posed in that year by Carlos Montúfar to the city where he lived and where he proved himself a skilful manipulator of the common people against the socalled "juntistas".